E3 Ubiquitin ligase RNF126 regulates the progression of tongue cancer. (26th May 2016) - Wang, Lina; Wang, Xin; Zhao, Yuehan; Niu, Weidong; Ma, Guowu; Yin, Wei; Shi, Chun
Abstract: This study aims to analyze the role of RNF126 in the oncogenesis of tongue cancer. The cell proliferation and viability of human tongue cancer cells, SCC25 and SCC9 cells, were determined by cell counting and MTT assay, respectively. The effect of RNF126 on regulating AKT signaling pathway was analyzed through western blotting. The transplantation tumor model of nude mice was used to evaluate the tumorigenecity of RNF126. Knockdown of RNF126 inhibited the proliferation and viability of SCC9 and SCC25 cells. Inhibition of RNF126 also decreased the activity of AKT1 as well as its downstream molecules. Furthermore, RNF126 regulated the tumor volume on mice model. These data suggested that RNF126 might be related to the progression of tongue cancer through regulating AKT signaling pathway. Abstract : Our data suggested that RNF126 might be related to the progression of tongue cancer through regulating AKT signaling pathway.